Molecular forms of butyrylcholinesterase and obesity - Boberg, Dellyana R. (Sociedade Brasileira de Genética, 2010)
This study compared obese (N = 134) and unobese (N = 92) male blood donors, regarding the relative intensity (RI) and activity of different molecular forms (G1, G2, G4 and G1-ALB) of butyrylcholinesterase (BChE, EC 3.1.1.8) found in plasma, thereby searching for an association between these variables with obesity and SNPs of exons 1 and 4 of the BCHE gene. It was shown that obese and unobese individuals do not differ in the RI of each BChE band, even when classifying the sample into three genotypes of exons 1 and 4 of the BCHE gene (-116GG/539AA, -116GG/539AT, -116GA/539AT). Although the mean BChE activity of each band was significantly higher in obese than in unobese blood donors, the proportions of BChE bands were maintained, even under the metabolic stress associated to obesity, thereby leading to infer that this proportion is somehow regulated, and may therefore be important for BChE functions.